Modelo geométrico de ordem k correlacionado - Souza, Roberta de (2019)
In this work we propose the correlated geometric distribution of order k, k≥1, with parameters π and ρ; π ∈(0,1), max{−1,−1−π π } ≤ρ < 1, as an extension of the generalized geometric distribution proposed by Philippou e Muwaﬁ (1980) and considering the ideas of Kolev, Minkova e Neytchev (2000) for generalizations of discrete distributions by including an additional parameter ρ. Thus, it is also a re-reading of the geometric distribution of order k by Aki e Hirano (1993). Some properties of the proposed distribution are presented. Regression models are developed using classical and Bayesian estimation methods. Simulated data studies show the behavior of the distributions and some properties of the estimators. The main motivation in this research, besides contribute to generalizations of discrete distributions, is to propose na alternative analysis and even more suitable for real data, since the effect of the individual correlation is taken into account through the existence of the parameter. The ﬁtted models are evaluated and the residual analysis and diagnosis of inﬂuence or divergence are also presented.